GAMBARAN PROTEKSI RADIASI PADA RUANGAN GENERAL X-RAY MERK TOSHIBA DI RUMAH SAKIT KHUSUS PARU MEDAN TAHUN 2022 - SAMUEL, SAMUEL (JURNAL ILMIAH MAKSITEK, 2023)
Radiation protection is an action taken to reduce the damaging effects of radiation due to radiation exposure. The aim of implementing protection and radiation is to prevent deterministic effects and reduce the opportunity for stochastic effects to occur. Thorax radiology examination in the ICU room with a non-cooperative patient. Patients in the ICU where it is not possible to carry out normal examinations according to theory and are non-cooperative, such as: unconscious patients, using ventilators or assistive devices for patients who have difficulty breathing. The aim of this research is to determine the study of radiation protection in the Thoshiba general X-ray room at the Medan Special Lung Hospital. implementation of radiation protection during thorax examinations using a mobile light aircraft in the Intensive Care Unit (ICU) of the Medan Special Lung Hospital. The research design used in this research is descriptive with an observational approach. This research method was carried out with the aim of creating an objective picture of a situation. This research was carried out by means of direct interviews with radiographers regarding the implementation of radiation protection during thorax examinations using a Thoshiba Brand x-ray aircraft at the Medan Special Lung Hospital. From the research results, it can be seen that thorax examinations in the Radiology Installation of the Medan Special Lung Hospital in 2022 have implemented radiation protection in the Thoshiba Brand X-Ray general room in the Radiology Installation of the Medan Special Lung Hospital in 2022. So in this study it can be concluded that radiation protection in in the Thoshiba Brand X-Ray general room in the Radiology Installation at the Medan Special Lung Hospital, it is in accordance with the Examination Operational Standards (SOP).